Energy balance analysis on Rimbo Dua palm oil - Arif Hidayat; Ari Wibowo; Saptyaji Harnowo (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
Palm Oil Mill is an industry that uses biomass as an energy generator to run the process. The biomass used is fiber, shells, and empty fruit bunches. Energy efficiency is needed in the process; therefore, it requires energy balance in the power generation system, distribution, and use of energy produced by biomass. PKS Rimbo Duo has a processing capacity of 30 tonnes/hour. Broadly speaking, the energy system at PKS Rimbo Dua includes steam energy production equipment such as boilers and steam and electricity energy conversion equipment in the form of steam turbines and generators (alternators) as well as storage equipment for the expansion of steam energy in the form of opposing pressure storage vessels (BPV). Energy balance analysis is carried out by analyzing data methods obtained from the performance of operating equipment and conducting field surveys and measurements of predetermined parameters, especially in boilers, water treatment, and turbines. Analysis of fuel use is also carried out to determine the quality of the fuel and the potential for steam produced. The result of this research is that the average efficiency of the boiler is 63.23%, which is still below the 73% boiler design. One of the reasons is that the flue gas temperature reaches 260 oC. The steam turbine has an efficiency of 44% isentropically with SSC = 31.9 kg / kWh when compared to the standard norm, the SSC value is still too high. The results of the water analysis also found the P and M alkalinity values, and the water pH was still 9.8. The results of the analysis of these data can be used as a reference for actions whether it is a repair of equipment, replacement of equipment, and improvement of operational parameters.